The Extended Stability of Cervical Swabs in careHPV™ Collection Medium - Cheng Siang, Tan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: The careHPV™ Test is a US FDA approved, CE mark, and WHO prequalified in vitro diagnostic test designed to screen for 14 high-risk human papillomavirus (HRHPV) genotypes. The careHPV™ Test is one of the commercial HPV test validated to be used in low resource settings, boasting the economy of processing a maximum of 90 samples per batch and a near point-of-care turnaround time of 3 hours. According to the manufacturer, cervical swabs stored in careHPV™ Collection Medium are stable for 30 days when stored between 2-8°C. However, we often had difficulty consolidating enough samples for a full batch-test within 30 days, especially when screening women living in the low-density villages in rural Sarawak, Malaysian Borneo. This study aimed to evaluate the stability and repeatability of cervical swabs preserved in careHPV™ Collection Medium stored at 4°C exceeding the recommended 30 days using the careHPV™ Test. Methods: Two groups of confirmed HRHPV-positive and HRHPV-negative cervical swab samples in careHPV™ Collection Medium consisting of 4 samples each were maintained at 4°C and tested using the careHPV™ Test at Day -38, -123, -131, -223, and -395. Results: All cervical swabs in the careHPV™ Collection Medium stored at 4°C remained stable for testing and demonstrated 100% repeatability for at least 395 days from the day of collection. Conclusion: The careHPV™ Test can be successfully performed on cervical swabs preserved in careHPV™ Collection Medium, which were stored at 4°C for at least 395 days.